Effect of picloram, additives and plant growth regulators on somatic embryogenesis of phyla nodiflora (L.) greene - Ahmed, A.B.A.; Rao, A.S.; Rao, M.V.; Taha, R.M. (2011)
The present study describes the plant regeneration via somatic embryogenesis in suspension culture derived from the leaf and stem explants of Phyla nodiflora. The medium type, plant growth regulators, complex extract (coconut milk and malt extract) and anti-oxidant (activated charcoal, ascorbic acid, Polyvinylpyrrolidone and citric acid) markedly influenced the embryo regeneration of P. nodiflora. MS with 2,4-D and activated charcoal (10 mg/L) gave the highest stimulation of embryogenic callus growth. Optimized callus was transfered into suspension culture, which showed the globular, heart shaped embryos in MS with 2,4-D + BA + picloram (0.1 mg/L), coconut milk (10 ml/L), citric acid (100 mg/L) on 6th subcultures. Further development stages such as torpedo and cotyledonary stage embryos and fostered maturation of embryos were observed at 8(th) and 10(th) subculture. However, the high frequency embryo germination and plantlet (45 plants/20 mg cotyledonary stages embryos) formation was obtained in half-strength MS medium without growth regulators from cotyledonary embryos. All the plantlets established in the field exhibited morphological characters similar to those of the mother plant.